Cd4+ T cell phenotypes, autoantibodies and transcriptional signatures overlap between myocarditis, ischemic and nonischemic heart failure, suggesting shared inflammatory pathogenic mechanisms. (3rd October 2022) - Sandel, C; Myers, J; Alvarez, K; Stavrakis, S; Gaffney, P; Cunningham, M
Abstract: Background: Myocarditis may progress to heart failure (HF) often as a result of viral myocardial infection where cardiomyocyte damage exposes sequestered self-antigens including cardiac myosin (CM) leading to autoimmunity. CM acts as an adjuvant via activation of Toll-like receptor (TLR)2 and TLR8, and is a potent autoantigen promoting HF in myocarditis through elevated IL-6, IL-17A and Th17 differentiation concomitant with autoantibody responses against CM. Since cardiomyocyte damage also occurs in ischemic and nonischemic cardiomyopathies, we investigated the hypothesis that ischemic and nonischemic HF would have similar inflammatory phenotypes. Purpose: We defined CD4+ T helper cell phenotypes, autoantibodies, and peripheral blood transcriptome of the inflammatory phenotypes in myocarditis, compared to ischemic, and nonischemic HF. The identification of immune phenotypes in myocarditis and HF are important for consideration of inflammatory interventions and immunotherapies in myocarditis and HF. Methods: Peripheral blood was collected from myocarditis patients within 6 months of disease onset, and from clinically stable, chronic HF patients. CD4+ T helper cells (Th1, Th2, and Th17) were evaluated by flow cytometry after density gradient separation, and human CM autoantibody titers were determined by ELISA. Whole blood RNA sequencing, Ingenuity Pathway Analysis (IPA), as well as multi-contrast pathway enrichment were performed. Results: (Fig. 1A) Significantly elevated human CM autoantibodies were observed in myocarditis, ischemic and nonischemic HF patients, and correlated with nonrecovered patients and poor outcomes. (Fig. 1B) Myocarditis and nonischemic HF patients had significantly elevated Th17 and Th2 frequencies. Ischemic HF patients had a trend toward elevated Th 17 and Th 2 CD4+ T cell frequencies. None of the cohorts demonstrated an elevation in Th1 (not shown) (Fig 2A), IPA canonical pathway enrichment for all cohorts together showed elevated pathways concordant with our proposed pathogenic mechanisms in myocarditis and HF, including TLR and inflammasome signaling and IL17A and IL13 pathways (Fig. 2B). Myocarditis and nonischemic HF shared more inflammatory pathway enrichment in common than ischemic HF (Fig. 2C) Multi contrast pathway enrichment demonstrated that males in each cohort shared TLR and IL1b signaling that was not observed in females. Conclusion: Nonischemic HF patients have overlapping immunological features with myocarditis including elevated anti-CM autoantibodies, as well as Th17, and Th2 frequencies. Ischemic HF demonstrated elevated CM autoantibodies and fewer inflammatory genes and pathways. The transcriptome supported the immune phenotypes in myocarditis and heart failure suggesting pathogenic autoimmune and inflammatory mechanisms shared in myocarditis and ischemic HF. The results have implications for immunomodulatory therapies in myocarditis and HF. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institutes of Health